Physical Quality and Number of Spores From Coffee Pulp Fermented with Trichoderma viride Based On The Number of Different Spores - Pratama, Said Mirza; Jamilah, Maryam (Universitas Bengkulu, 2024)
Using coffee pulp as an alternative feed for ruminant livestock is one solution that can be used to overcome the problem of fluctuating green feed availability. The primary and sustainable goal to be achieved is the intensification and expansion of plantation waste based on Coffee pulp as an alternative feed to increase the utility of Coffee pulp. The specific target to be achieved is to determine the ability of T.viride with various concentrations to improve physical quality and the ability of molds to maintain their population so that they can produce good quality animal feed with good physical condition to support livestock productivity and growth. This study used a Completely Randomized Design (CRD) consisting of 4 treatments with four replications. The treatment consisted of 0 spores/ml, 105 spores/ml, 106 spores/ml, and 107 spores/ml of T. viride addition. The parameters observed were physical quality (color, texture, odor), pH, and number of spores. Based on the research that has been conducted, it can be concluded that the best treatment of T. viride mold to support a good coffee pulp fermentation process is at a dose of 107 spores/ml of water.